Effect of Pesticide Residues on Health and Different Enzyme Levels in the Milk of Women from Karachi-Pakistan - Uzma Mehboob,; Mohammad Ahmed Azmi,; Mohammad Arshad Azmi ,; Syed Naeem ul Hasan Naqvi, (Journal of Basic & Applied Sciences, 2012)
The aim of this study was to investigate the presence of pesticide residues in human milk and their effects on the enzyme levels (cholinesterase and lactate dehydrogenase) as well as the health status of the pesticide exposed women. Total 135 milk samples from 45 women were collected from nine different divisions of Karachi, Pakistan. In addition ten milk samples were also collected from normal subjects. The milk samples were taken at day 1, day 15 and day 30 from the same women and from the same divisions. The data indicated that only cypermethrin, deltamethrin, malathion and match were identified. The highest concentration 34.86 µg/10 µl of deltamethrin and the lowest concentration 0.336 µg/10 µl of cypermethrin was found in the milk sample. It may be concluded that exposed women showed significant increased and decreased enzyme levels at different division and also complained about the disturbance in the normal functioning of different organ system and possibly produced various ailments and clinically suffered with skin diseases, backache, disturbance in micturition, difficulty in breathing, asthma and hepatitis.